Evolutionary integration and modularity in the diversity of the suckermouth armoured catfishes - Corinthia R. Black; Jonathan W. Armbruster (Royal Society Open Science, 2022)
The evolution of morphological diversity has held a long-standing fascination among scientists. In particular, do bodies evolve as single, integrated units or do different body parts evolve semi-independently (modules)? Suckermouth armoured catfishes (Loricariidae) have a morphology that lends nicely to evolutionary modularity and integration studies. In addition to a ventrally facing oral jaw that directly contacts surfaces, the neurocranium and pectoral girdle are fused, which limits movement of the anterior part of the body. Functional constraints suggest it is likely the head and post-cranial body act as separate modules that can evolve independently. If true, one would expect to see a two- or three-module system where the head and post-cranial body are morphologically distinct. To test this hypothesis, we quantified shape using geometric morphometric analysis and assessed the degree of modularity across functionally important regions. We found the armoured catfish body is highly modularized, with varying degrees of integration between each module. Within subfamilies, there are different patterns of evolutionary modularity and integration, suggesting that the various patterns may have driven diversification along a single trajectory in each subfamily. This study suggests the evolution of armoured catfish diversification is complex, with morphological evolution influenced by interactions within and between modules.